Issues in the development of open access to research data. (1st March 2014) - Wessels, Bridgette; Finn, Rachel L.; Linde, Peter; Mazzetti, Paolo; Nativi, Stefano; Riley, Susan; Smallwood, Rod; Taylor, Mark J.; Tsoukala, Victoria; Wadhwa, Kush; Wyatt, Sally
Abstract : This paper explores key issues in the development of open access to research data. The use of digital means for developing, storing and manipulating data is creating a focus on 'data-driven science'. One aspect of this focus is the development of 'open access' to research data. Open access to research data refers to the way in which various types of data are openly available to public and private stakeholders, user communities and citizens. Open access to research data, however, involves more than simply providing easier and wider access to data for potential user groups. The development of open access requires attention to the ways data are considered in different areas of research. We identify how open access is being unevenly developed across the research environment and the consequences this has in terms of generating data gaps. Data gaps refer to the way data becomes detached from published conclusions. To address these issues, we examine four main areas in developing open access to research data: stakeholder roles and values; technological requirements for managing and sharing data; legal and ethical regulations and procedures; institutional roles and policy frameworks. We conclude that problems of variability and consistency across the open access ecosystem need to be addressed within and between these areas to ensure that risks surrounding a data gap are managed in open access.